PENGARUH EDUKASI KESEHATAN MELALUI MEDIA VIDEO TENTANG PENCEGAHAN ANEMIA TERHADAP PENGETAHUAN DAN SIKAP REMAJA PUTRI DI SMA NEGERI 6 KOTA TANJUNGPINANG - Ria Elfira; Susanti, Susanti; Ribut Sulistyawati, Tri (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2025)
ABSTRACT Anemia is a serious nutritional problem among adolescent girls. This condition occurs due to iron deficiency in the body. A lack of knowledge and attitude regarding anemia prevention among adolescent girls is one of the main contributing factors. Its impact can disrupt learning concentration, physical growth, brain development, and weaken the immune system. Therefore, health education through video media can be an effective method in preventing anemia. This study aimed to determine the effect of health education using video media on the knowledge and attitudes of adolescent girls in preventing anemia. The study used a quantitative method with a pre-experimental approach and a one-group pretest-posttest design. The population consisted of all female students in grades X and XI at SMA Negeri 6 Kota Tanjungpinang, totaling 80 individuals, used total sampling. Data were collected using a questionnaire and analyzed with the Wilcoxon Signed Rank Test. The average knowledge score increased from 12.17 to 18.83, and the attitude score increased from 38.10 to 78.49. The analysis results using the Wilcoxon Signed Rank Test showed that health education using video media had an effect on knowledge (p-value = 0.000) and attitude (p-value = 0.000) of adolescent girls in preventing anemia at SMA Negeri 6 Kota Tanjungpinang. In conclusion, health education using video media has a significant effect and can improve the knowledge and attitudes of adolescent girls in preventing anemia. This study recommends video media as an effective means of health education to enhance knowledge and attitudes among adolescent girls in anemia prevention. Keywords : Anemia, Video Media, Knowledge, Attitude